Screening of hearing loss in neonates and infants: a hospital based prospective study - Rajashekhar, Rashmi P.; Karodpati, Nayanna S.; Rajashekar, Prashant; Sonar, Tejal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Approximately 12,000 new babies with hearing loss are identified every year, according to the National Institute on Deafness and other communication disorders. In addition, estimates are that another 4,000 to 6,000 infants and young children between birth and 3 years of age who passed the newborn screening test acquire late onset hearing loss. Therefore, 16,000 to 18,000 new babies and toddlers are identified with hearing loss per year making hearing loss the most common birth defect. Numerous studies over the decades have demonstrated that when hearing loss of any degree is not adequately diagnosed and treated, it can negatively affect the speech, language, academic, emotional and psychosocial development of young children. Hence, the most important aspect of managing a child with hearing loss is early identification. Methods: The screening test was done on high risk neonates and neonates admitted in NICU for more than 48 hours from January 2018 to June 2019 for early detection of hearing loss if any. Results: Our results showed that neonates with hyperbilirubinaemia, Low birth weight , birth asphyxia , meconium aspiration showed higher risk of hearing loss as the Oto Acoustic Emissions were absent in significant percentage of these high risk neonates and infants as compared to neonates without NICU admission. Conclusions: Screening of high-risk neonates and infants is essential for early detection of hearing loss. Hence preventing the child from further developing profound hearing loss with loss of speech.